Mapping chemistry learning difficulties of secondary school students: a cross-grade study - Pratomo, Heru; Fitriyana, Nur; Wiyarsi, Antuni; Marfuatun, Marfuatun (Intelektual Pustaka Media Utama, 2025)
Students' lack of interest in chemistry becomes a significant issue in chemistry learning. This may be caused by the negative perception of students about their difficulties in learning chemistry. This study aims to explore views and causes of difficulties in learning chemistry from the perspective of secondary school students. This research was designed using a survey method through a cross-grade study. The sample that participated in this study was 634 students from the Grade 10, 11, and 12 (G10, G11, and G12) of secondary school students in Yogyakarta, Indonesia, through random sampling. The data in this study were collected using the chemistry difficulties scale (CDS) and chemistry perception questions (CPQ). Statistical descriptive techniques, a one-way multivariate analysis of variance (MANOVA) test, and content analysis, were used to analyse the research data. The results showed that the grade somewhat affected students' views towards chemistry. They viewed chemistry as a fairly difficult subject, with stoichiometry, thermochemistry, and macromolecule being among the most challenging topics in G10, G11, and G12, respectively. These difficulties are caused by scientific language, mathematical abilities, student abilities, and teacher competence in conducting chemistry lessons. Since the students consider chemistry somewhat difficult, chemistry teachers must take appropriate strategies to overcome these difficulties.